2001
DOI: 10.1093/ajcn/73.2.465s
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and safety

Abstract: Bacterial species that have traditionally been regarded as safe are used in probiotics; the main strains used include lactic acid bacteria and bifidobacteria that inhabit the intestinal tracts of humans and animals. However, reports of frequent isolation of bacteria used in probiotics from infection sources in recent years have raised much debate over the safety of probiotics. This article describes the status quo of isolation of probiotic bacteria from infections and reviews each of the factors that have to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
164
0
10

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(184 citation statements)
references
References 42 publications
1
164
0
10
Order By: Relevance
“…The results in this study are in conformity with the findings of Jin et al (1997) who reported that administration of Lactobacilli through feed had a positive effect on feed intake and feed conversion efficiency. It was hypothesized that using probiotic at a dosage not above the lethal dose (>1×10 11 CFU/kg) in diets would increase the nutrient retention and decrease their passage rate as undigested feed through maintaining balanced natural microbiota which would reduce the feed intake (Ishibashi and Yamazaki, 2001;Altaf et al, 2009). Heart weight showed no significant effect of L. acidophilus supplemented feed.…”
Section: Discussionmentioning
confidence: 99%
“…The results in this study are in conformity with the findings of Jin et al (1997) who reported that administration of Lactobacilli through feed had a positive effect on feed intake and feed conversion efficiency. It was hypothesized that using probiotic at a dosage not above the lethal dose (>1×10 11 CFU/kg) in diets would increase the nutrient retention and decrease their passage rate as undigested feed through maintaining balanced natural microbiota which would reduce the feed intake (Ishibashi and Yamazaki, 2001;Altaf et al, 2009). Heart weight showed no significant effect of L. acidophilus supplemented feed.…”
Section: Discussionmentioning
confidence: 99%
“…At present, criteria defining the safety of probiotics for aquaculture are urgently needed. In food and pharmaceutical industries, the factors that must be addressed in the evaluation of safety of probiotics include pathogenicity, infectivity, toxicity, metabolic activity, and the intrinsic properties of the microbes (Ishibashi and Yamazaki, 2001). Moreover, commercial probiotics produced in other countries actually introduces exotic microorganisms.…”
Section: Commercial Probioticsmentioning
confidence: 99%
“…This commensal intestinal microbiota is essential as they protect the host against infections and maintain the body's homeostasis under normal circumstances (Gaggia et al, 2010). Among the numerous intestinal microbes, Lactobacillus, Bifidobacterium and Enterococcus have been demonstrated to affect the host beneficially by improving the intestinal microbial balance and hence are categorized as probiotics (Ishibashi & Yamazaki, 2001). Among several enterococcal species, Enterococcus faecium and Enterococcus faecalis are the two predominant species in the human intestine (Giraffa, 2003).…”
Section: Introductionmentioning
confidence: 99%